Case Report: Bordetella bronchiseptica Meningoencephalomyelitis in a Dog - Rylander, Helena; Djani, Dylan M.; Cameron, Starr (Frontiers in Veterinary Science, 2022)
A 15-month-old male neutered Wirehaired Pointer mixed-breed dog presented with fever and cervical pain. Cerebrospinal fluid (CSF) analysis showed neutrophilic pleocytosis with intracellular bacteria, and culture of CSF grew Bordetella bronchiseptica. The patient became non-ambulatory 3 days after CSF collection. He was treated with low-dose prednisone for 3.5 months and doxycycline for 1 year. Recheck CSF analysis 1 month after diagnosis showed reduction of inflammation and 3 months after diagnosis revealed only increased protein. The patient improved neurologically over several months and was weakly ambulatory 5 months and fully ambulatory 7 months after diagnosis. Whole genome sequencing of the bacterial isolate and a live modified intranasal vaccine similar to the one the dog had been vaccinated with 7 weeks prior to diagnosis was similar but not an exact match. Bacterial meningitis should be considered, and culture of CSF is recommended, in cases of neutrophilic pleocytosis of CSF.